Changing regional images; are regional marketing campaigns successful? - Wilhelm J. Meester; Pieter H. Pellenbarg (European Regional Science Association (ERSA), 2001)
An important element in the urban and regional development strategy of many local and regional governments is geographical marketing. The process of geographical marketing combines promotional, spatial and organisational activities, and can be aimed at various groups. In 1989 a marketing campaign was started by the province of Groningen, in the northern part of the Netherlands. This campaign, which is still being carried on, has used various means of communication: advertisements in newspapers and magazines, and radio and television commercials. It has been aimed at entrepreneurs and at the general public as well. An ex ante study of the public image of Groningen was carried out before the start of the campaign. For this purpose a random sample of the Dutch population was inquired by telephone. Since then similar inquiries were carried out every two years, in order to measure the effects of the campaign. In these inquiries the image of the provinces of Friesland and Noord-Brabant was measured along with that of Groningen, and used for reference. The availability of this kind of data for a period of twelve years, measured at regular intervals, provides an opportunity to study the development of regional images through time. In this paper the data of the inquiries will be analysed. One of the main questions to be answered in the paper relates to the pace and the nature of the changes in image, observed in all three provinces. The second question specifically deals with the influence of the marketing campaign on the image of Groningen.
Keywords: 330